ANALYTICAL REVIEW ON THE MODERN OPTIMIZATION ALGORITHMS IN LOGISTICS - Zaher, Akkad Mohammad; Bányai, Tamás (Advanced Logistic Systems - Theory and Practice, 2021)
Optimization algorithms are used to reach the optimum solution from a set of available alternatives within a short time relatively. With having complex problems in the logistics area, the optimization algorithms evolved from traditional mathematical approaches to modern ones that use heuristic and metaheuristic approaches. Within this paper, the authors present an analytical review that includes illustrative and content analysis for the used modern algorithms in the logistics area. The analysis shows accelerated progress in using the heuristic/metaheuristic algorithms for logistics applications. It also shows the strong presence of hybrid algorithms that use heuristic and metaheuristic approaches. Those hybrid algorithms are providing very efficient results.